Investigation of the Relationship Between Economic Growth and use of Fossil and Hydroelectric Energy Resources by ARDL Boundary Test: 1971-2018 Iraq Case - Rogash Younis Masiha; Sadeq Taha Abdulazeez; Dindar Saeed Saeed (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2021)
Energy is an important input for economies. In this context, many countries have conducted studies to examine how energy affects their economies. In addition, the relationship between energy and economic growth is an important indicator in guiding economic policies. In this study, the effect of Energy Production from Fossil Sources (EPFS) and Energy Production from Hydroelectric Sources (EPHS) on Economic Growth (GDP) for Iraq was analyzed with the ARDL Cointegration test. The data of Iraq used in the study were taken from the official web address of the World Bank and covers the years between 1971-2018. A significant and positive relationship has been found between the energy resources discussed in the study and economic growth. In addition, according to the Toda-Yamamoto causality analysis, a causality relationship from the use of fossil energy resources to economic growth was found. Likewise, a causality relationship has been found from the use of hydroelectric energy resources to economic growth.